2019
DOI: 10.1007/s10806-019-09806-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Concerns in Poultry Production: A German Consumer Survey About Dual Purpose Chickens

Abstract: The paper offers insights into the acceptability of ethical issues in poultry production and how this situation provides an opportunity to transform the prevailing system into a more sustainable one. The survey among German consumers reveals that killing day-old chicks is a well-known practice and is rated as "very problematic". In contrast, dual-purpose chickens are mostly unknown but are considered a positive alternative to killing day-old chicks (after the concept has been explained). Consumer clusters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
1
26
0
3
Order By: Relevance
“…Finally, it is important to mention that consumers see the concept of dual-purpose breeds as a more animal-friendly practice [1,5,47,48] for which they would be willing to pay a higher price if meat quality is improved while their expectations on animal welfare are met [1,4,5]. Additionally, studies have shown that consumers are willing to pay more for regional products [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to mention that consumers see the concept of dual-purpose breeds as a more animal-friendly practice [1,5,47,48] for which they would be willing to pay a higher price if meat quality is improved while their expectations on animal welfare are met [1,4,5]. Additionally, studies have shown that consumers are willing to pay more for regional products [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Among these alternatives is the use of dual-purpose breeds (DPBs) that can be used for egg production (female animals) and broiler production (male animals) (Damme 2015;Krautwald-Junghanns et al 2018). However, the concept of DPBs is not familiar to most consumers (Gangnat et al 2018;Brümmer et al 2017;Busse et al 2019). Nonetheless, when introduced to this alternative, consumers see it as a positive practice that is more animal-friendly and ethically justifiable (Gangnat et al 2018;Brümmer et al 2017;Leenstra et al 2011;Busse et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the concept of DPBs is not familiar to most consumers (Gangnat et al 2018;Brümmer et al 2017;Busse et al 2019). Nonetheless, when introduced to this alternative, consumers see it as a positive practice that is more animal-friendly and ethically justifiable (Gangnat et al 2018;Brümmer et al 2017;Leenstra et al 2011;Busse et al 2019). Nowadays, there are commercial DPBs available such as Lohmann Dual (Lohmann Tierzucht GmbH, Cuxhaven, Germany), and traditional DPBs that have a lower fattening/laying performance (Mueller et al 2018), for example Vorwerkhuhn, which are used rarely on farms.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is associated with both ethical and economic issues in modern egg production as 50% of hatched eggs are wasted. A recent survey among 1000 German consumers shows that 67% of them find the practice of killing day-old chicks ‘very problematic’ [ 5 ]. As some countries, like Germany and France, have taken initiatives on a national level to ban the practice of killing of day-old male layer chicks by 2022 [ 6 , 7 , 8 ], solutions for handling the male layer chickens are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits of such strategies have not been assessed in the light of consumer/citizen expectations or in comparison to slow-growing broilers reared outdoors. Most consumers, e.g., 82% of German consumers [ 5 ], are not familiar with dual-purpose poultry, i.e., both meat and egg production can be carried out by the same genotype.…”
Section: Introductionmentioning
confidence: 99%